Salmonella Kentucky: Antimicrobial resistance and molecular analysis of clinical, animal and environment isolates, Morocco - Karraouan, Bouchra; Ziyate, Nadia; Ed-dra, Abdelaziz; Amajoud, Nadia; Boutaib, Rachid; Akil, Abdellah; El Allaoui, Abdellah; El Ossmani, Hicham; Zerouali, Khalid; Elmdaghri, Naima; Bouchrif, Brahim (The Journal of Infection in Developing Countries, 2017)
This item has no abstract. Follow the links on the page to access the full text.